Human Resources Empowerment, Working Motivation and Organization Change in Improving Hotel Business Performance in Bali - Sutawa, Gusti Kade; Bendesa, , I Komang Gde; Madiun, I Nyoman (E-Journal of Tourism; Volume 1 Number 2 (September 2014), 2014)
This study aims to test and analyze impact of human resource development on working motivation of hotel business workers in Bali, impact of human resource development on organizational changes of hotel business in Bali, impact of human resource development on the performance of hotel business in Bali, impact of working motivation against organizational changes in hotel business in Bali, impact of working motivation on the organizations performance of the hotel business in Bali, and impact of organizational changes against organizations performance of the hotel business in Bali. There were 170 respondents of star-rated hotel employees which were selected through purposive sampling technique. Structural Equation Modeling with the application Analysis of Moment Structure was used to analyze the data. The results show that empowerment of human resources (HR) has positive and significant impact on working motivation, organizational changes, and the organization performance of hotel business in Bali, working motivation has positive and significant impact on organizational changes and the organization performance of hotel business in Bali and organizational changes have significant and positive impact on the organization performance of hotel business in Bali. Empowerment variables have the most powerful impact to support the improvement of organizational performance, followed by organizational changes and working motivation variables. The results indicate that human resource empowerment improves the performance of the hotel business in Bali. Therefore, human resource development need to be prioritized in order to improve organizational performance of star hotels in Bali.
Keywords: human resource empowerment, working motivation, organizational changes, organizational performance